Problem Kewenangan Mahkamah Konstitusi Memutus Perselisihan Hasil Pilkada - Albab AF, M. Abid Ulil (Jurnal Hukum & Pembangunan, 2018)
Initially the election was included in the regional autonomy government regime, so that the settlement of election disputes was under the authority of the Supreme Court. Then the legislators put the election into the electoral regime and formed Law No. 12 of 2008 concerning Regional Government which in Article 236C of the Law states that the settlement of election disputes was transferred and resolved in the Constitutional Court. On May 19, 2014 the Constitutional Court granted the examination of Article 236 C of Law No. 12 of 2008 related to the authority of the Constitutional Court to decide on disputes over election results, because the Constitutional Court considered that the article was contradictory to the 1945 Constitution (unconstitutional). In Islamic law when there are regional head elections which then lead to disputes about who is a legitimate leader who has the right to receive bai'at, it must be proven through examination of witnesses and evidence. For this reason, it must be known in advance about who is most authorized to try the matter, whether the Supreme Court or the Constitutional Court.